OCORRÊNCIA DE Biomphalaria straminea Dunker, 1948 (Gastropoda, Planorbidae) NA REGIÃO NEUSTÔNICA DE UM RESERVATÓRIO DO SEMIÁRIDO: SERIA UMA FORMA DE DISPERSÃO? - Medeiros, Íttalo Luã Silva; Morais Junior, Cláudio Simões de; Júnior, Mauro de Melo (Revista Nordestina de Zoologia, 2016)
Planorbid molluscs are gastropods commonly found in continental northeastern aquatic environments. Due their scraping habit, adults adhere to drifting surfaces, like vegetal parts, animal bodies and boats hull, ensuring their dispersal. However, little is known about the dispersion of their juvenile forms. In this sense, the objective of this work is to report, for the first time, the occurrence of juvenile forms of Biomphalaria straminea in the neustonic region of a Brazilian semiarid reservoir (Serrinha II, Pernambuco), as well as to investigate possible reletionships with some abiotic parameters. For this, 100L of surface water were filteres at 12 points along the entire reservoir. B. straminea juveniles were recorded in the 10 points of the reservoir studied, with higher abundances at the central stations and more downstream. Negative correlations between abundace and the variables electrical conductivity and turbidity were observed. Due to its wide distribution in the neuston layer of the studied reservoir, and greater concentrations in the central zones and near the spillway, that is, área more downstream to the flow of the ecosystem, it is probable that this species does presente this form of dispersion. Future experimental stuides may bring new clues about this type of disperse behavior.